PERAN ORANG TUA DALAM PENGENDALIAN PENGGUNAAN GADGET SERTA DAMPAKNYA TERHADAP PERKEMBANGAN ANAK USIA DINI DI PAUD AL-KAMAL JAMPANGTENGAH KABUPATEN SUKABUMI - Irma Muti; Jimatul Arrobi; Ismatul Maula; Erna Hoerunisa; Sintani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has significantly increased gadget usage among early childhood children, particularly following the COVID-19 pandemic. This phenomenon requires active parental involvement to ensure that digital exposure does not negatively affect child development. This study aims to analyze parental roles in controlling gadget usage and its impact on early childhood development at PAUD Al-Kamal Jampangtengah, Sukabumi Regency. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Participants consisted of parents and teachers selected through purposive sampling. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings indicate that parental control strategies include time limitation, active mediation, content selection, and total restriction. Active mediation and selective educational content were found to positively influence children's social, emotional, language, cognitive, and behavioral development. In contrast, uncontrolled usage or restrictive prohibition without communication tends to result in negative responses, including reduced social interaction and dependency behaviors. The study concludes that the effectiveness of gadget control is not solely determined by screen time duration but largely depends on the quality of parental mediation and interaction during digital engagement.